2013
DOI: 10.1515/crelle-2013-0030
|View full text |Cite
|
Sign up to set email alerts
|

A uniqueness theorem for Frobenius manifolds and Gromov–Witten theory for orbifold projective lines

Abstract: We prove that the Frobenius structure constructed from the Gromov-Witten theory for an orbifold projective line with at most three orbifold points is uniquely determined by the Witten-Dijkgraaf-Verlinde-Verlinde equations with certain natural initial conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 14 publications
4
28
0
Order By: Relevance
“…For the cases that χ A > 0 by [9,10,7] and the cases that χ A = 0 by [17], same statements as Theorem 4.1 are shown. Therefore, combining them with Theorem 4.1, it is shown that, for arbitrary triplet of positive integers A, there exists the classical mirror symmetry between the orbifold projective line with at most three orbifold points P 1 A and the pair of the cusp polynomial f A and the primitive form ζ A associated to it.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…For the cases that χ A > 0 by [9,10,7] and the cases that χ A = 0 by [17], same statements as Theorem 4.1 are shown. Therefore, combining them with Theorem 4.1, it is shown that, for arbitrary triplet of positive integers A, there exists the classical mirror symmetry between the orbifold projective line with at most three orbifold points P 1 A and the pair of the cusp polynomial f A and the primitive form ζ A associated to it.…”
Section: Introductionmentioning
confidence: 53%
“…In our previous paper [6], it is shown that a Frobenius structure with certain conditions can be reconstructed uniquely and the one constructed from the Gromov-Witten theory of the orbifold projective line P 1 A with arbitrary triplet of positive integers A satisfies the conditions. We shall see the Frobenius structure constructed from the pair (f A , ζ A ) also satisfies the conditions, i.e., the following Theorem 4.2 holds:…”
Section: Exists An Isomorphism Of Frobenius Manifolds Between the Onementioning
confidence: 99%
See 3 more Smart Citations